2017
DOI: 10.3389/fpsyt.2017.00184
|View full text |Cite
|
Sign up to set email alerts
|

Possible Facilitative Effects of Repeated Anodal Transcranial Direct Current Stimulation on Functional Outcome 1 Month Later in Schizophrenia: An Open Trial

Abstract: Recent research on neuromodulation techniques, such as transcranial direct current stimulation (tDCS), for the treatment of schizophrenia has mainly focused on psychotic symptoms. We aimed to determine whether repetitive tDCS is efficacious in improving determinants of outcome, such as cognitive function, daily living skills, and depressive mood in patients with schizophrenia. Twenty-eight patients underwent tDCS (2 mA × 20 min) two times per day for 5 consecutive days. The anodal electrode was placed over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…29 Indeed, anodal stimulation over the left prefrontal cortex in schizophrenia patients showed an improvement in the functional capacity and depressive symptoms. 30 This lends support for tDCS's treatment potential for those with LLD as a monotherapy or augmentation with antidepressants. However, it should be noted that controversial findings observed no antidepressant differences between active and sham tDCS for depression.…”
Section: Stimulation Target In Depression-dlpfcmentioning
confidence: 76%
See 1 more Smart Citation
“…29 Indeed, anodal stimulation over the left prefrontal cortex in schizophrenia patients showed an improvement in the functional capacity and depressive symptoms. 30 This lends support for tDCS's treatment potential for those with LLD as a monotherapy or augmentation with antidepressants. However, it should be noted that controversial findings observed no antidepressant differences between active and sham tDCS for depression.…”
Section: Stimulation Target In Depression-dlpfcmentioning
confidence: 76%
“…Furthermore, a reduction in executive deficits in patients with LLD may indirectly alleviate the depressive symptoms and enhance the treatment response . Indeed, anodal stimulation over the left prefrontal cortex in schizophrenia patients showed an improvement in the functional capacity and depressive symptoms . This lends support for tDCS's treatment potential for those with LLD as a monotherapy or augmentation with antidepressants.…”
Section: Introductionmentioning
confidence: 78%
“…The dose of neuroleptics will not be changed during the study period. In our pilot study ( 22 ), mean and SD of change from baseline of the UPSA-B was 11.68 (9.84) in patients scoring lower than 80 at baseline. We conservatively hypothesized that 9.00, the lower limit of 50% confidence interval of mean change from baseline in the pilot study, would be the mean difference between two groups in this study.…”
Section: Materials and Equipmentmentioning
confidence: 67%
“…In a previous open trial, we demonstrated the ability of tDCS to improve functional capacity, as well as depressive symptoms, in patients with schizophrenia ( 22 ). However, since this was a pilot study with a single arm, conducting a controlled trial is desirable.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation